The essential oil constituents of Artabotrys species – A review - Subban, Ravi; Kaveri, Sundaram (Journal of Phytology, 2020)
Artabotrys species which belongs to Annonaceae family are pleasant smelling and it is attributed to the presence of mono and sesquiterpenoids present in the essential oil of the plant. The objective of the present work is to review the chemical composition of the essential oils reported from twenty different Artabotrys species from various parts of the world. In the various Artabotrys species, the major compounds are monoterpene and sesquiterpene hydrocarbons and oxygenated sesquiterpenes. The frequently and most commonly identified constituents are β-caryophyllene, caryophyllene oxide, 3-Carene, cyperene, cyperenone and 1,5-epoxy-salvial4(14)-ene. Other constituents seems to be more specific to the respective Artabotrys species.